Among the Methods for Improving the English Terminology is Word-Formation - Murotova Xayotxon; Maksudova Shakhnoza (Journal of Innovation in Education and Social Research, 2023)
The study of word formation is one method to improve the vocabulary in English. The average speaker typically takes the rules governing the creation of new words and their adoption into the language for granted. This article explores these rules.